How the West became antisemitic: Jews and the formation of Europe, 800-1500 - Marcus, Ivan G. (Princeton University Press, 2024)
An examination of how the Jews-real and imagined-so challenged the Christian majority in medieval Europe that it became a society that was religiously and culturally antisemitic in new ways In medieval Europe, Jews were not passive victims of the Christian community, as is often assumed, but rather were startlingly assertive, forming a Jewish civilization within Latin Christian society. Both Jews and Christians considered themselves to be Gods chosen people. These dueling claims fueled the rise of both cultures as they became rivals for supremacy. In How the West Became Antisemitic, Ivan Marcus shows how Christian and Jewish competition in medieval Europe laid the foundation for modern antisemitism.Marcus explains that Jews accepted Christians as misguided practitioners of their ancestral customs, but regarded Christianity as idolatry. Christians, on the other hand, looked at Jews themselves-not Judaism-as despised. They directed their hatred at a real and imagined Jew: theoretically subordinate, but sometimes assertive, an implacable enemy within. In their view, Jews were permanently and physically Jewish-impossible to convert to Christianity. Thus Christians came to hate Jews first for religious reasons, and eventually for racial ones. Even when Jews no longer lived among them, medieval Christians could not forget their former neighbors. Modern antisemitism, based on the imagined Jew as powerful and world dominating, is a transformation of this medieval hatred.A sweeping and well-documented history of the rivalry between Jewish and Christian civilizations during the making of Europe, How the West Became Antisemitic is an ambitious new interpretation of the medieval world and its impact on modernity